Effects of cold press time on compressive strength, deformation rates and soaked properties of biomass brick. (20th March 2018) - Lu, Zeguang; Wang, Meng; Jia, Wanda
Highlights: Compressive strengths of dried and soaked bricks are significantly affected by cold press time. Deformation rates of dried brick in thickness are significantly affected by cold press time. Water absorption content of soaked brick for 168 h is great, which averages 45.23%. Dimension stability of the soaked brick is good. The densities of soaked bricks for 168 h are slightly affected by cold press time. Abstract: Corn stalk and waster poplar fibers can be molded into brick for building in order to increase their value. To explore effects of cold press time on the quality of brick, compressive strength, deformation rates and soaked properties are studied. Compressive strengths of dried and soaked bricks are significantly affected by cold press time. Wet compressive strength of the soaked brick is greater than compressive strength of the dried brick. Deformation rates of dried brick in length and width are slightly affected by cold press time and the rates in thickness are significantly affected by cold press time. Water absorption content of soaked brick is great, dimension stability of soaked brick is good. The densities of soaked bricks are slightly affected by cold press time. Compressive strengths of dried bricks average 1.33 MPa. To soaked bricks for 168 h, the pore rates average 40.55%, water absorption contents average 45.23%, densities average 1.42 g/cm 3, deformation rates average 0.54% in length, 0.71% in width and 2.08% in thickness, and wet compressive strengths average 1.17 MPa. It is an effective way to increase the compressive strength by prolonging the cold press time, which provides a basic theory for the manufacture and application of brick.